Factors for consumer choice of dairy products in Iran. (1st April 2017) - Rahnama, Hassan; Rajabpour, Shayan
Abstract: Little is known about consumers' behavior especially their choice behavior toward purchasing and consuming dairy products in developing countries. Hence, the aim of the present work is understanding the factors that affect on consumers' choice behavior toward dairy products in Iran. The study applies the theory of consumption values, which includes the functional values (taste, price, health, and body weight), social value, emotional value, conditional value and epistemic value. The sample were 1420 people (men and women). The data was collected using face to face survey in summer and fall 2015. Chi-square, confirmatory factor analysis, and structural equation modelling is used to assess data collected. The results indicate that functional values, social value, emotional value and epistemic value have a positive impact on choosing dairy products and conditional value didn't have a positive impact. It was concluded that the main influential factors for consumers' choice behavior toward dairy products included consumers experience positive emotion (e.g. enjoyment, pleasure, comfort and feeling relaxed) and functional value-health. This study emphasized the proper pricing of dairy products by producers and sellers.